*This preview shows
pages
1–3. Sign up
to
view the full content.*

This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
**Unformatted text preview: **ECE 309 — Electromagnetic Fields University of Virginia Fall 2008 Homework # 1 Solutions 1. There are a number of ways to approach this problem. We are given that ~ A is a known vector and ~ X is an unknown vector. Also, the following products are known, p = ~ A · ~ X and ~ B = ~ A × ~ X To find ~ X , we need to find a basis — that is, a set of vectors that can be used to express ~ X . Since p is the projection of ~ A onto ~ X , ~ A is an easy choice for one of the basis vectors. Also note that the vector ~ B × ~ A is perpendicular to ~ A (and also to ~ B ). Thus we can use this as the second basis vector and write ~ X as, ~ X = a ~ A + b ( ~ B × ~ A ) where a and b are constants (scalars) that we need to find. Consider the dot product given above, p = ~ A · ~ X = a ~ A · ~ A + b ~ A · ( ~ B × ~ A ) The last term above is zero (because ~ A is perpendicular to the vector ~ B × ~ A ), so noting that ~ A · ~ A = A 2 , a = p A 2 Now let’s consider the cross product, ~ B = ~ A × ~ X = a ~ A × ~ A + b ~ A × ( ~ B × ~ A ) Noting that ~ A × ~ A = 0 and using the vector identity, ~ A × ( ~ B × ~ C ) = ~ B ( ~ A · ~ C )- ~ C ( ~ A · ~ B ) we have ~ B = ~ A × ~ X = b ~ B ( ~ A · ~ A )- ~ A ( ~ A · ~ B ) Again the last term is zero because ~ A and ~ B are perpendicular. Thus, b = 1 A 2 and we have, ~ X = p ~ A + ~ B × ~ A A 2 Note that a quicker way to the answer is to expand ~ A × ~ B , and use the identity we exploited previously (with ~ X replacing ~ C ): ~ A × ~ B = ~ A × ( ~ A × ~ X ) = ~ A ( ~ A · ~ X )- ~ X ( ~ A · ~ A ) = p ~ A- A 2 ~ X Now, we can solve for ~ X algebraically, ~ X = p ~ A + ~ B × ~ A A 2 , as before! 2. To take the gradients, let’s write the vector ~ r in Cartesian coordinates, ~ r = ( x- x )ˆ x + ( y- y )ˆ y + ( z- z )ˆ z Thus, ~ ∇ ( r 2 ) = ~ ∇ ( x- x ) 2 + ( y- y ) 2 + ( z- z ) 2 = ˆ x ∂ ∂x ( x- x ) 2 +ˆ y ∂ ∂y ( y- y ) 2 +ˆ z ∂ ∂z ( z- z ) 2 = 2 ( x- x )ˆ x +( y- y )ˆ y +( z- z...

View
Full
Document